Analysis of Communication in Problem-Based Mathematics Learning through Transcript Based Lesson Analysis (TBLA) - Filda Wulan Damayanti; Nur Fauziyah; Syaiful Huda (USN Kolaka, 2021)
This study aims to describe communication in problem-based mathematics learning through TBLA and the learning tendencies based on the results of the analysis of Transcript Based Lesson Analysis (TBLA). This type of research is descriptive exploratory research with a qualitative approach. The subjects of this study were all students of class VIII-D UPT SMP Negeri 1 Gresik which consisted of 32 students. The supporting instruments in this study consisted of documentation using an audio-visual recording device and sheets for lesson analysis the TBLA model. From the results of the TBLA analysis, both based on the number of letters and categorization, it can be seen that problem-based mathematics learning tends to be dominated by students. In the results of the TBLA analysis based on the number of letters, it can be seen that students are active in communicating with other students or group members, only occasionally asking the teacher about things that need explanation. Likewise, the results of the TBLA analysis based on categorization show that the initiation of students in communicating is greater as shown in PM1 and PM2 around 80% compared to teacher initiation shown in PG1 to PG7 of around 20%. This shows that the interaction communication between teachers and students in problem-based mathematics learning in the classroom is more dominated by students. So that problem-based mathematics learning tends to be student centered learning.